A Study on the Significance of Aristotle Western Philosophy: An Exploration of Aristotle's Contributions to Western Philosophy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Greek philosopher Aristotle (384-322 B.C.) made significant and lasting contributions to nearly every aspect of human knowledge, from logic to biology to ethics and aesthetics. Though overshadowed in classical times by the work of his teacher Plato, from late antiquity through the Enlightenment, Aristotle’s surviving writings were incredibly influential. In Arabic philosophy, he was known simply as “The First Teacher” in the West, he was “The Philosopher.”Aristotle was born in 384 B.C. in Stagira in northern Greece. Both of his parents were members of traditional medical families, and his father, Nicomachus, served as court physician to King Amyntus III of Macedonia. His parents died while he was young, and he was likely raised at his family’s home in Stagira. At age 17 he was sent to Athens to enroll in Plato’s Academy. He spent 20 years as a student and teacher at the school, emerging with both a great respect and a good deal of criticism for his teacher’s theories.